Method for liquid-phase oxidative decomposition of vanadium slag under low alkalinity
By using liquid phase oxidation method to decompose vanadium slag at low alkalinity, the problems of low vanadium recovery, inability to recover chromium, high energy consumption and environmental pollution in the traditional sodium calcination method are solved, and efficient recycling and environmental protection processes of vanadium and chromium are achieved.
Patent Information
- Application Number
- CN202510093922.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
AI Technical Summary
The traditional sodium roasting method has a low vanadium recovery rate during vanadium extraction process, which cannot recover chromium resources, and high-temperature energy consumption, which produces harmful gases and is seriously polluted to the environment.
The liquid phase oxidation method at low alkalinity is used to decompose vanadium slag. After stirring the sodium hydroxide solution with the vanadium slag in an autoclave, the reaction temperature, pressure, time and other conditions are controlled to achieve the oxidation and decomposition of vanadium and chromium and recover resources.
It significantly reduces energy consumption, improves the resource utilization rate of vanadium and chromium, reduces the vanadium and chromium content in the tailings, achieves efficient recycling of vanadium and chromium, and avoids the generation of harmful gases, which has environmental advantages.
Smart Images

Figure CN119913372A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical tailings extraction, and more specifically, relates to a method for liquid phase oxidation decomposition of vanadium slag under low alkalinity. Background Art
[0002] Vanadium is a key alloying element, mainly used in the steel industry. Vanadium-containing steel has the characteristics of high strength, excellent toughness and wear resistance, so it is widely used in machinery, automobiles, shipbuilding, railways, aviation, bridges, electronic technology, defense industry and other fields. The demand for vanadium in the steel industry directly affects the market conditions of the vanadium market. About 10% of vanadium is used to produce titanium alloys required by the aerospace industry, where vanadium acts as a stabilizer and strengthener, giving titanium alloys good ductility and plasticity. In addition, in the chemical industry, vanadium is mainly used as a catalyst and colorant. Vanadium is also used in the production of rechargeable hydrogen batteries or vanadium redox batteries. Vanadium slag mainly comes from the tailings of the steel industry, in which the original ore contains chromium. Since vanadium and chromium have similar properties, chromium resources also enter the vanadium slag.
[0003] The traditional vanadium slag vanadium extraction process adopts the sodium method roasting method, the main principle of which is to add additives such as sodium carbonate or sodium hydroxide to the vanadium slag, convert the low-valent vanadium in the vanadium slag into pentavalent vanadium through high-temperature roasting, and then obtain a vanadium-containing leachate by water leaching. Subsequently, ammonium salt is added to the leachate to produce a precipitate of ammonium polyvanadate, which is then roasted to obtain a vanadium oxide product. However, the vanadium recovery rate of this method is only about 70%, and chromium resources cannot be recovered, resulting in a waste of resources. In addition, the temperature of the sodium method roasting is too high, and multiple roastings are required, which has high energy consumption. Harmful toxic gases such as HCI and Cl2 may be produced during the roasting process, causing environmental pollution. Summary of the invention
[0004] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0005] In order to achieve these purposes and other advantages according to the present invention, a method for liquid phase oxidation decomposition of vanadium slag under low basicity is provided, comprising the following steps:
[0006] Step 1, preparing sodium hydroxide solution;
[0007] Step 2, adding a certain amount of vanadium slag to the sodium hydroxide solution prepared in step 1 in proportion, and stirring evenly to obtain a mixed solution; the vanadium slag is derived from vanadium-titanium magnetite, and is produced through a blast furnace or direct reduction process to produce pig iron (water) containing vanadium (chromium), and then using oxygen or air as an oxidizing medium under high temperature conditions, and adopting a production process such as shaking ladle vanadium extraction, hot metal ladle vanadium extraction, and various top-blown and combined-blown converter vanadium extraction;
[0008] Step 3, adding the stirred mixed solution into a high-pressure reactor, controlling the reaction temperature, reaction pressure, reaction time, oxygen rate, and rotation speed, and waiting for the reaction to end; during the reaction, the low-valent vanadium in the vanadium slag is oxidized to high-valent vanadium to generate sodium vanadate; at the same time, the trivalent chromium in the vanadium slag is oxidized to hexavalent chromium to generate sodium chromate;
[0009] Step 4: After the reaction is completed, the mixed solution is filtered while hot to obtain a mixed solution of sodium vanadate and sodium chromate, and the vanadium and chromium in the vanadium slag are recovered into the sodium vanadate solution and the sodium chromate solution respectively, so as to achieve the purpose of recovering vanadium and chromium resources.
[0010] Preferably, in step 1, industrial-grade sodium hydroxide is used to prepare a sodium hydroxide solution with a mass fraction of 10% to 20%. Compared with the previous method of leaching using a high-alkalinity sodium hydroxide solution, this method is more conducive to the subsequent vanadium-chromium separation operation.
[0011] Preferably, the ratio of the amount of sodium hydroxide and the amount of vanadium slag to the alkali ore is 1:1 to 1:4.
[0012] Preferably, the reaction pressure in step three is in the range of 1.5 MPa to 4 MPa.
[0013] Preferably, the reaction time in step three is 2 h to 6 h.
[0014] Preferably, the reaction temperature in step three is 150°C to 250°C.
[0015] Preferably, the oxygen rate in step three is maintained in the range of 0.5 to 1 L / min.
[0016] Preferably, the stirring speed in step three is maintained in the range of 600 to 1200 r / min.
[0017] Preferably, in said step 4, the mixed liquid is filtered while hot, and the liquid temperature ranges from 75°C to 95°C.
[0018] Preferably, the components in the mixed solution after the reaction include: a total V content of 10 g / L to 20 g / L in terms of V2O5, and a total Cr content of 5 g / L to 15 g / L in terms of Cr2O3.
[0019] In step 2, before adding the sodium hydroxide solution, the vanadium slag is pretreated to obtain vanadium slag modified by mixing hexadecyltrimethylammonium bromide and molybdenum trioxide. The pretreatment method of the vanadium slag includes:
[0020] S1. Weigh vanadium slag with a particle size of less than 200 meshes, add it to anhydrous ethanol, and disperse it at an ultrasonic frequency of 50 to 80 kHz for 20 to 40 minutes to obtain a vanadium slag dispersion, wherein the mass volume ratio of the vanadium slag to the anhydrous ethanol is 1 to 5 g: 25 to 50 mL; add 0.5% to 1% of the mass of the vanadium slag hexadecyl trimethylammonium bromide to the dispersion, and stir at a speed of 200 to 600 rpm to completely dissolve the hexadecyl trimethylammonium bromide, and then disperse it at an ultrasonic frequency of 50 to 80 kHz for 20 to 40 minutes, and let it stand for 12 to 36 hours to obtain a slurry dispersion;
[0021] S2. Add 0.8% to 1.5% of the mass of vanadium slag N,N-ethylenebisstearamide and MoO3 powder with a particle size of 50 to 100 nm to the slurry dispersion after standing, the mass of MoO3 powder accounts for 0.2% to 1.5% of the mass of vanadium slag, and after stirring and dispersing, heat to 60 to 90°C, keep warm for 1 to 3 hours, and then heat to 90 to 100°C for evaporation and concentration, wash with deionized water, and dry to obtain the pretreated vanadium slag.
[0022] The present invention has at least the following beneficial effects:
[0023] The present invention uses liquid phase oxidation to decompose vanadium slag in a low concentration NaOH system, and the reaction temperature is 200-220° C. Compared with the high temperature required by the traditional sodium roasting process, it is reduced by more than 600° C., thereby significantly saving energy consumption.
[0024] The method of the invention has a high utilization rate of vanadium and chromium resources. After liquid phase oxidation decomposition, the vanadium content in the tailings is 1-2wt% (in terms of V2O5) and the chromium content is 2-3wt% (in terms of Cr2O3).
[0025] The method of the present invention does not generate dust harmful to human body and environment during the liquid phase oxidation process, and is therefore a very environmentally friendly method.
[0026] Before the vanadium slag is mixed with a sodium hydroxide solution for liquid phase oxidation, the vanadium slag is pretreated; first, quaternary ammonium salt hexadecyltrimethylammonium bromide is used as a dispersant to slurry and disperse the vanadium slag, thereby reducing the agglomeration between the vanadium slag powders and improving the uniformity of the particle size distribution of the vanadium slag powders; then, N,N-ethylenebisstearamide is used to surface modify the vanadium slag powder to increase the surface area of the vanadium slag powder; finally, a catalyst MoO3 powder is introduced to fully mix the MoO3 powder with the vanadium slag powder; the vanadium slag powder after the above pretreatment has a larger oxygen contact area and a faster oxidation reaction rate, thereby improving the oxidation conversion rate of low-valent chromium and low-valent vanadium, reducing the vanadium-chromium content in the tailings, and improving the recovery rate of vanadium-chromium.
[0027] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The present invention is a process flow chart of the method for decomposing vanadium slag by liquid phase oxidation. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0030] It should be understood that terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0031] Example 1
[0032] The vanadium slag used in this embodiment is produced from vanadium (chromium) containing pig iron (water) produced from vanadium-titanium magnetite by a blast furnace process, and then formed by a shaking bag vanadium extraction process under high temperature conditions with air as an oxidizing medium.
[0033] like Figure 1 As shown, this embodiment provides a method for liquid phase oxidation decomposition of vanadium slag under low basicity, comprising the following steps:
[0034] Step 1. First, prepare the reaction materials: weigh the materials according to the mass ratio of NaOH to vanadium slag of 0.3:1; weigh 200g of vanadium slag less than 200 mesh (the V2O5 content in the vanadium slag is 17.77wt%, and the Cr2O3 content is 6.04wt%), and 60g of NaOH; prepare sodium hydroxide into a solution with a mass fraction of 10%.
[0035] Step 2, liquid phase oxidation reaction: place the NaOH solution and vanadium slag prepared in step 1 in a high-pressure reactor, set the reaction temperature to 200°C, set the stirring speed to 600r / min, and start heating; after rising to 200°C, introduce oxygen at a rate of 0.5L / min and maintain the pressure at 2MPa, and react for 6 hours under complete mixing conditions.
[0036] Step 3, filtration and separation: The reaction slurry of step 2 is filtered and separated at 90°C to obtain tailings and an aqueous solution containing vanadium and chromium. The tailings are fully washed and dried and then tested to determine the total vanadium content: 3.27wt% (in terms of V2O5) and the total chromium content: 4.01wt% (in terms of Cr2O3); the vanadium recovery rate of this embodiment is 83.45%, and the chromium recovery rate is 40.24%.
[0037] Example 2
[0038] The vanadium slag used in this embodiment is produced from vanadium-titanium magnetite by a blast furnace process to produce vanadium (chromium)-containing pig iron (water), and then formed by a shaking bag vanadium extraction process under high temperature conditions with air as an oxidizing medium.
[0039] This embodiment provides a method for liquid phase oxidation decomposition of vanadium slag under low basicity, comprising the following steps:
[0040] Step 1. First, prepare the reaction materials: weigh the materials according to the mass ratio of NaOH to vanadium slag of 0.5:1; weigh 100g of vanadium slag less than 200 mesh (the V2O5 content in the vanadium slag is 17.77wt%, and the Cr2O3 content is 6.04wt%), and 50g of NaOH; prepare sodium hydroxide into a solution with a mass fraction of 10%.
[0041] Step 2, liquid phase oxidation reaction: place the NaOH solution and vanadium slag prepared in step 1 in a high-pressure reactor, set the reaction temperature to 200°C, set the stirring speed to 600r / min, and start heating; raise the temperature to 200°C, introduce oxygen at a rate of 0.5L / min and maintain the pressure at 2MPa, and react for 6 hours under complete mixing conditions.
[0042] Step 3, filtration and separation: The reaction slurry of step 2 is filtered and separated at 90°C to obtain tailings and an aqueous solution containing vanadium and chromium. The tailings are fully washed and dried and then tested to determine the total vanadium content: 2.57wt% (in terms of V2O5) and the total chromium content: 3.57wt% (in terms of Cr2O3); the vanadium recovery rate of this embodiment is 86.98%, and the chromium recovery rate is 46.80%.
[0043] Example 3
[0044] The vanadium slag used in this embodiment is produced from vanadium-titanium magnetite by a blast furnace process to produce vanadium (chromium)-containing pig iron (water), and then formed by a shaking bag vanadium extraction process under high temperature conditions with air as an oxidizing medium.
[0045] Step 1. First, prepare the reaction materials: weigh the materials according to the mass ratio of NaOH to vanadium slag of 0.7:1; weigh 100g of vanadium slag less than 200 mesh (the V2O5 content in the vanadium slag is 17.77wt%, and the Cr2O3 content is 6.04wt%), and 70g of NaOH; prepare sodium hydroxide into a solution with a mass fraction of 10%.
[0046] Step 2, liquid phase oxidation reaction: place the NaOH solution and vanadium slag prepared in step 1 in a high-pressure reactor, set the reaction temperature to 200°C, set the stirring speed to 600r / min, and start heating; raise the temperature to 200°C, introduce oxygen at a rate of 0.5L / min and maintain the pressure at 2MPa, and react for 6 hours under complete mixing conditions.
[0047] Step 3, filtration and separation: The reaction slurry of step 2 is filtered and separated at 90°C to obtain tailings and an aqueous solution containing vanadium and chromium. The tailings are fully washed and dried and then tested to determine the total vanadium content: 2.21wt% (in terms of V2O5) and the total chromium content: 3.21wt% (in terms of Cr2O3); the vanadium recovery rate of this embodiment is 88.81%, and the chromium recovery rate is 52.17%.
[0048] Example 4
[0049] The vanadium slag used in this embodiment is produced from vanadium-titanium magnetite by a blast furnace process to produce vanadium (chromium)-containing pig iron (water), and then formed by a shaking bag vanadium extraction process under high temperature conditions with air as an oxidizing medium.
[0050] This embodiment provides a method for liquid phase oxidation decomposition of vanadium slag under low basicity, comprising the following steps:
[0051] Step 1. First, prepare the reaction materials: weigh the materials according to the mass ratio of NaOH to vanadium slag of 1:1; weigh 100g of vanadium slag less than 200 mesh (the V2O5 content in the vanadium slag is 17.77wt%, and the Cr2O3 content is 6.04wt%), and 100g of NaOH; prepare sodium hydroxide into a solution with a mass fraction of 10%.
[0052] Step 2, liquid phase oxidation reaction: place the NaOH solution and vanadium slag prepared in step 1 in a high-pressure reactor, set the reaction temperature to 200°C, set the stirring speed to 600r / min, and start heating; raise the temperature to 200°C, introduce oxygen at a rate of 0.5L / min and maintain the pressure at 2MPa, and react for 6 hours under complete mixing conditions.
[0053] Step 3, filtration and separation: The reaction slurry of step 2 is filtered and separated at 90°C to obtain tailings and an aqueous solution containing vanadium and chromium. The tailings are fully washed and dried and then tested to determine the total vanadium content: 2.01wt% (in terms of V2O5) and the total chromium content: 2.91wt% (in terms of Cr2O3); the vanadium recovery rate of this embodiment is 89.82%, and the chromium recovery rate is 56.64%.
[0054] Example 5
[0055] The vanadium slag used in this embodiment is produced from vanadium-titanium magnetite by a blast furnace process to produce vanadium (chromium)-containing pig iron (water), and then formed by a shaking bag vanadium extraction process under high temperature conditions with air as an oxidizing medium.
[0056] This embodiment provides a method for liquid phase oxidation decomposition of vanadium slag under low basicity, comprising the following steps:
[0057] Step 1. First, prepare the reaction materials: weigh the materials according to the mass ratio of NaOH to vanadium slag of 1:1; weigh 100g of vanadium slag less than 200 mesh (the V2O5 content in the vanadium slag is 17.77wt%, and the Cr2O3 content is 6.04wt%), and 100g of NaOH; prepare sodium hydroxide into a solution with a mass fraction of 15%.
[0058] Step 2, liquid phase oxidation reaction: place the NaOH solution and vanadium slag prepared in step 1 in a high-pressure reactor, set the reaction temperature to 200°C, set the stirring speed to 600r / min, and start heating; raise the temperature to 200°C, introduce oxygen at a rate of 0.5L / min and maintain the pressure at 2MPa, and react for 6 hours under complete mixing conditions.
[0059] Step 3, filtration and separation: The reaction slurry of step 2 is filtered and separated at 90°C to obtain tailings and an aqueous solution containing vanadium and chromium. The tailings are fully washed and dried and then tested to determine the total vanadium content: 1.71wt% (in terms of V2O5) and the total chromium content: 2.53wt% (in terms of Cr2O3); the vanadium recovery rate of this embodiment is 91.34%, and the chromium recovery rate is 62.31%.
[0060] Example 6
[0061] This embodiment provides a method for liquid phase oxidation decomposition of vanadium slag under low basicity, which is different from Example 5 in that, in step 1, 100 g of vanadium slag with a particle size of less than 200 mesh (the V2O5 content in the vanadium slag is 17.77 wt %, and the Cr2O3 content is 6.04 wt %) is pretreated to obtain vanadium slag modified by mixing hexadecyltrimethylammonium bromide and molybdenum trioxide, and then the pretreated vanadium slag is mixed with 100 g of a solution prepared by NaOH with a mass fraction of 15%, and a liquid phase oxidation reaction is carried out in an autoclave. The pretreatment method of the vanadium slag comprises:
[0062] S1. Weigh 100 g of vanadium slag with a particle size of less than 200 mesh, add it to 3000 mL of anhydrous ethanol, disperse it at an ultrasonic frequency of 80 kHz for 20 minutes to obtain a vanadium slag dispersion, add 1 g of hexadecyltrimethylammonium bromide to the vanadium slag dispersion, stir it at a speed of 500 rpm to completely dissolve the hexadecyltrimethylammonium bromide, then disperse it at an ultrasonic frequency of 60 kHz for 40 minutes, let it stand for 12 hours, and obtain a slurry dispersion;
[0063] S2. Add 1 g of N,N-ethylenebisstearamide and 1.5 g of MoO3 powder with a particle size of 50-100 nm to the slurry dispersion after standing, stir and disperse, heat to 80°C, keep warm for 3 hours, then raise the temperature to 100°C for evaporation and concentration, wash with deionized water, and dry to obtain the pretreated vanadium slag.
[0064] The methods and process parameters of the remaining steps of this embodiment are the same as those of embodiment 5. The tailings obtained in this embodiment are fully washed and dried and then tested to determine the total vanadium content: 0.63wt% (in terms of V2O5) and the total chromium content: 1.17wt% (in terms of Cr2O3); the vanadium recovery rate of this embodiment is 97.82%, and the chromium recovery rate is 83.51%.
[0065] Example 7
[0066] This embodiment provides a method for liquid phase oxidation decomposition of vanadium slag under low basicity, which is different from Example 5 in that, in step 1, 100 g of vanadium slag with a particle size of less than 200 mesh (the V2O5 content in the vanadium slag is 17.77 wt %, and the Cr2O3 content is 6.04 wt %) is pretreated to obtain vanadium slag modified by mixing hexadecyltrimethylammonium bromide and molybdenum trioxide, and then the pretreated vanadium slag is mixed with 100 g of a solution prepared by NaOH with a mass fraction of 15%, and a liquid phase oxidation reaction is carried out in an autoclave. The pretreatment method of the vanadium slag comprises:
[0067] S1. Weigh 100 g of vanadium slag with a particle size of less than 200 mesh, add it to 2500 mL of anhydrous ethanol, and disperse it at an ultrasonic frequency of 60 kHz for 40 minutes to obtain a vanadium slag dispersion; add 0.5 g of hexadecyltrimethylammonium bromide to the vanadium slag dispersion, stir it at a speed of 600 rpm, dissolve the hexadecyltrimethylammonium bromide completely, and then disperse it at an ultrasonic frequency of 580 kHz for 40 minutes, let it stand for 12 hours, and obtain a slurry dispersion;
[0068] S2. Add 1g of N,N-ethylenebisstearamide and 1g of MoO3 powder with a particle size of 50-100nm to the slurry dispersion after standing, stir and disperse, heat to 60-90°C, keep warm for 1-3h, then heat to 90-100°C, evaporate and concentrate, wash with deionized water, and dry to obtain pretreated vanadium slag.
[0069] The methods and process parameters of the remaining steps of this embodiment are the same as those of embodiment 5. The tailings obtained in this embodiment are fully washed and dried and then tested to determine the total vanadium content: 0.58wt% (in terms of V2O5) and the total chromium content: 1.03wt% (in terms of Cr2O3); the vanadium recovery rate of this embodiment is 98.16%, and the chromium recovery rate is 86.31%.
[0070] Comparative Example 1
[0071] This comparative example provides a method for liquid phase oxidation decomposition of vanadium slag under low basicity. Compared with Example 6, the pretreatment method of vanadium slag is replaced by:
[0072] 100 g of vanadium slag with a particle size less than 200 mesh (the V2O5 content in the vanadium slag is 17.77 wt%, the Cr2O3 content is 6.04 wt%), 1 g of hexadecyltrimethylammonium bromide, 1 g of N,N-ethylenebisstearamide and 1.5 g of MoO3 powder with a particle size of 50 to 100 nm are weighed and mixed to obtain a mixed powder, and then the pretreated vanadium slag is mixed with a 15% solution prepared by 100 g of NaOH sodium hydroxide with the mixed powder, and a liquid phase oxidation reaction is carried out in an autoclave.
[0073] The remaining steps and process parameters of this comparative example are the same as those of Example 5. The tailings obtained in this comparative example were fully washed and dried and then tested, and the total vanadium content was 1.56wt% (in terms of V2O5) and the total chromium content was 1.98wt% (in terms of Cr2O3). The vanadium recovery rate of this comparative example was 92.47%, and the chromium recovery rate was 70.33%.
[0074] Comparative Example 2
[0075] This comparative example provides a method for liquid phase oxidation decomposition of vanadium slag under low basicity. Compared with Example 6, the pretreatment method of vanadium slag is replaced by:
[0076] 100 g of vanadium slag with a particle size of less than 200 meshes was weighed and added to 2500 mL of anhydrous ethanol, and dispersed at an ultrasonic frequency of 60 kHz for 40 minutes to obtain a vanadium slag dispersion; 0.5 g of hexadecyltrimethylammonium bromide was added to the vanadium slag dispersion, and stirred at a speed of 600 rpm to completely dissolve the hexadecyltrimethylammonium bromide, and then dispersed at an ultrasonic frequency of 580 kHz for 40 minutes, and allowed to stand for 12 hours to obtain a slurry dispersion; the slurry dispersion was evaporated and concentrated, washed with deionized water, and dried to obtain a pretreated vanadium slag, and then the pretreated vanadium slag was mixed with a solution prepared by 100 g of NaOH with a mass fraction of 15%, and a liquid-phase oxidation reaction was carried out in an autoclave.
[0077] The methods and process parameters of the remaining steps of this comparative example are the same as those of Example 5. The tailings obtained in this comparative example were fully washed and dried and then tested, and the total vanadium content was 1.27wt% (in terms of V2O5) and the total chromium content was 1.60wt% (in terms of Cr2O3); the vanadium recovery rate of this comparative example was 93.28%, and the chromium recovery rate was 74.92%.
[0078] Comparative Example 3
[0079] This comparative example provides a method for liquid phase oxidation decomposition of vanadium slag under low basicity. Compared with Example 6, the pretreatment method of vanadium slag is replaced by:
[0080] Weigh 100g of vanadium slag with a particle size of less than 200 meshes and add it to 2500mL of anhydrous ethanol, disperse it at an ultrasonic frequency of 60kHz for 40min to obtain a vanadium slag dispersion; add 1g of N,N-ethylenebisstearamide and 1.5g of MoO3 powder with a particle size of 50-100nm to the vanadium slag dispersion, stir and disperse it, heat it to 80℃, keep it warm for 3h, then heat it to 100℃, evaporate and concentrate it, wash it with deionized water, and dry it to obtain the pretreated vanadium slag. Then mix the pretreated vanadium slag with a solution of 15% by mass prepared by 100g of NaOH sodium hydroxide, and carry out liquid phase oxidation reaction in an autoclave.
[0081] The methods and process parameters of the remaining steps of this comparative example are the same as those of Example 5. The tailings obtained in this comparative example were fully washed and dried and then tested, and the total vanadium content was 1.15wt% (in terms of V2O5) and the total chromium content was 2.18wt% (in terms of Cr2O3); the vanadium recovery rate of this comparative example was 94.36%, and the chromium recovery rate was 66.14%.
[0082] The number of devices and processing scales described here are used to simplify the description of the present invention. Applications, modifications and variations of the present invention will be obvious to those skilled in the art.
[0083] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for decomposing vanadium slag by liquid phase oxidation at low basicity, characterized in that: The following steps are involved: Step 1, preparing sodium hydroxide solution; Step 2: adding a certain amount of vanadium slag to the sodium hydroxide solution prepared in step 1 according to a certain proportion, and stirring evenly to obtain a mixed solution; Step 3, adding the stirred mixed solution into the high-pressure reactor, controlling the reaction temperature, reaction pressure, reaction time, oxygen rate, rotation speed, and waiting for the reaction to end; Step 4: After the reaction is completed, the mixed solution is filtered while hot to obtain a mixed solution of sodium vanadate and sodium chromate, and the vanadium and chromium in the vanadium slag are respectively recovered into the mixed solution of sodium vanadate and sodium chromate, thereby achieving the purpose of recovering vanadium and chromium resources.
2. The method for liquid phase oxidation decomposition of vanadium slag under low basicity as claimed in claim 1, characterized in that in the step 1, industrial grade sodium hydroxide is used to prepare a sodium hydroxide solution with a mass fraction of 10% to 20%.
3. The method for decomposing vanadium slag by liquid phase oxidation at low basicity as claimed in claim 1, characterized in that: The ratio of alkali ore to sodium hydroxide and vanadium slag is 1:1 to 1:
4.
4. The method for decomposing vanadium slag by liquid phase oxidation at low basicity as claimed in claim 1, characterized in that: The reaction pressure in step three is in the range of 1.5 MPa to 4 MPa.
5. The method for decomposing vanadium slag by liquid phase oxidation at low basicity as claimed in claim 1, characterized in that: The reaction time in step 3 is 2 h to 6 h.
6. The method for decomposing vanadium slag by liquid phase oxidation at low basicity as claimed in claim 1, characterized in that: The reaction temperature in step 3 is 150°C to 250°C.
7. The method for decomposing vanadium slag by liquid phase oxidation at low basicity as claimed in claim 1, characterized in that: The oxygen rate in step three is maintained in the range of 0.5 to 1 L / min.
8. The method for decomposing vanadium slag by liquid phase oxidation at low basicity as claimed in claim 1, characterized in that: The stirring speed in step 3 is maintained in the range of 600 to 1200 r / min.
9. The method for decomposing vanadium slag by liquid phase oxidation at low basicity as claimed in claim 1, characterized in that: In the step 4, the mixed liquid is filtered while hot, and the liquid temperature ranges from 75°C to 95°C.
10. The method for decomposing vanadium slag by liquid phase oxidation at low basicity according to claim 1, characterized in that: The components in the mixed solution after the reaction include: a total V content of 10 g / L to 20 g / L calculated as V2O5, and a total Cr content of 5 g / L to 15 g / L calculated as Cr2O3.